HEDONISTIC LIFESTYLE : CUSTOMERS BEHAVIORAL IN USING FINTECH WITH TAM MODEL - Puspitasari, Ratih Hesty Utami; Akbar, Shofif Sobaruddin; Nugraheni, Nadea Lathifah (Stability: Journal of Management and Business, 2024)
The development of the digital era has brought significant changes in the dynamics of economic trends, and the central role of consumers has shifted to digital technology. The Governor of Bank Indonesia gave an example, digital transactions in Indonesia increased by 46.72% and the use of digital banking increased by 25%. After the Covid-19 pandemic, consumers are accustomed to shopping online or e-commerce. This habit has been carried over to the present with the ease of shopping, the availability of buy now pay later payments or often called Paylater, and the existence of online loans that are currently developing, changing consumer lifestyle behavior. The ease of online shopping transactions accompanied by the benefits that consumers get such as free shipping makes consumers unaware that they have actually spent more money to buy the products or services they need. This type of consumer behavior is included in the hedonistic consumer type. Students are teenagers who are most often influenced by modernization. The existence of modernization and technological advances along with the development of the times will have an impact on the lifestyle and behavior of students.. Hedonistic behavior of students can be easily found in life, many students often spend time outside just to have fun with their friends, whether it's just hanging out in cafes, shopping at the mall.